Size, spillovers and soft budget constraints - Ernesto Crivelli; Klaas Staal (Max Planck Institute for Research on Collective Goods, 2008)
There is much evidence against the so-called too big to fail hypothesis in the case of bailouts to subnational governments. We look at a model where districts of different size provide local public goods with positive spillovers. Matching grants of a central government can induce so-cially-efficient provision, but districts can still exploit the intervening central government by induc-ing direct financing. We show that the ability and willingness of a district to induce a bailout and district size are negatively correlated. We also discuss the effect economies of scale in local public goods provision has on the bailout policies and argue that these policies can be subgame perfect equilibrium strategies.
Keywords: H4; H7; R1; 330; bailouts; soft-budget constraints; district size; spillovers; Gemeindefinanzen; Großstadt; Budgetrestriktion; Finanzausgleich; Lokales öffentliches Gut; Spillover-Effekt; Theorie